Analisis Standar Operasional Prosedur (Divisi Keuangan) Dalam Perspektif Islam pada Karyawan PT Prima Multi Terminal - Egita Pradila; Kamilah Kamilah (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study uses a qualitative approach and uses data collection methods in the form of direct field observations, interviews, and documentation. This study involved representatives from the finance department of PT Prima Multi Terminal. The results of this study only produced one standard operating procedure, namely systems and procedures for the financial division, cash receipts and disbursements/banks. With the implementation of the SOP, it is hoped that the bookkeeping can be updated on time, while other SOPs are still in the preparation stage, and it is hoped that similar work will not happen again between employees and publish reports in a timely and complete manner. An increasingly competitive business demands new companies, especially startups, to set rules and policies in running their business. All companies in service, trading and manufacturing need to do this in order for the company to run smoothly. Keywords: SOP, SOP (Financial Division), SOP in Islamic Perspective